Kita: The young ones - Afiq Nazmi, *; Chin, Capri *; Elza Irdalynna, *; Wong, Ivan *; Bonno, Jackson *; Davis, Nicholas *; Ooi, Ruby *; Sharifah Sofia, *; Sunitha Nayar, *; Chai, Valerie *; Martin, Yasmin *; Leow, Puay Tin * (Sunway University Department of Performance and Media, 2007)
Devised theatre featuring stories based on current issues and themes affecting the young. Contents: Runway girl. - The family. - The Torchlight piece. - A 'deadly' cardgame. - Solo pieces.